2022
DOI: 10.1017/s1368980022000052
|View full text |Cite
|
Sign up to set email alerts
|

Implications of updated protocol for classification of childhood malnutrition and service delivery in world’s largest refugee camp amid this COVID-19 pandemic

Abstract: Objectives: During the COVID-19 pandemic, the authorities made a change in the classification of malnutrition and concomitant service delivery protocol among the Rohingya children, residing in world’s largest refugee camp, located in Bangladesh. In this paper, we discussed the potential implications of this updated protocol on the malnutrition status among children from the Rohingya camp. Design: This paper reviewed relevant literature and authors’ own experience to provide a perspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Worsening of mental health conditions during the COVID-19 pandemic can be a particular concern among the displaced and refugee population, partly because of their unsuitable living condition, lack of access to health services, material deprivation, isolation, and uncertainty in their life (Anwar et al, 2022 ; Júnior et al, 2020 ; Singh et al, 2018 ; Spiritus-Beerden et al, 2021 ). Evidence showed that the prevalence of mental health problems among refugee population varied from 20% to 80% globally (Júnior et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Worsening of mental health conditions during the COVID-19 pandemic can be a particular concern among the displaced and refugee population, partly because of their unsuitable living condition, lack of access to health services, material deprivation, isolation, and uncertainty in their life (Anwar et al, 2022 ; Júnior et al, 2020 ; Singh et al, 2018 ; Spiritus-Beerden et al, 2021 ). Evidence showed that the prevalence of mental health problems among refugee population varied from 20% to 80% globally (Júnior et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%